STEM Teachers' Digital Competence: Different Subjects, Different Proficiencies - Rui Marques Vieira; Celina C. Tenreiro-Vieira; Pedro Bem-Haja; Margarida Lucas (MDPI AG, 2023)
STEM-science, technology, engineering, and mathematics-and STEM literacy have emerged as one (of many) concerted efforts aiming to provide the different competences required for future generations to adapt to an evolving world. Despite lacking a comprehensive framework for STEM, this concept has been studied under different perspectives, one of which is the digital competences of teachers. This study focuses on the digital competence and proficiency of 20,935 teachers, distributed across the following subjects: mathematics and natural sciences, physics and chemistry, biology and geology, and mathematics. It uses DigCompEdu as a conceptual framework to describe teachers' use of digital technologies to teach STEM subjects. The results show that biology and geology teachers achieved significantly higher digital proficiency scores when compared to teachers from the other three subjects. Physics and chemistry teachers also scores significantly higher than mathematics and natural sciences teachers. The results show the existence of significant positive correlations among all competence areas for the four STEM subjects. In conclusion, Portuguese teachers presented different levels of digital competence and perceived themselves as differently prepared for integrating digital technologies. A potential implication of this study is the need for teacher education about digital competences and a focus on producing teachers capable of dealing with STEM in their future classroom teaching and learning.